Comparative Analysis of Structural Reinforcement with Viscoelastic Energy Dissipators, Friction and Metal Creep in Tall Buildings - Lipa, Eddie J. (2024)
Seismic risk is a challenging problem in tall buildings due to the possibility of loss of human life and economic caused by seismic events. Peru is located at the interaction of the South American plate and the Nazca plate, which is why various seismic events of moderate to large magnitude occur. Today there are many ways to solve these problems and it is a very challenging case to reinforce tall buildings. In addition, technological advances in software facilitate and help through programmed models in tall buildings that analyze their structure characteristics such as drift, shear and others. This article proposes a comparative analysis of three types of dissipators: viscous fluid, friction, and metal creep through a Time-History analysis in a 15-story high-rise building located in Peru. The proposed methodology considers three stages: (i) definition of the characteristics and properties of the structure in accordance with Peruvian Standard E.030, in addition three accelerograms are used for the dynamic time-history analysis and maximum displacements and drifts are determined by ETABS software. (ii) calculate the design drift of the tall building and the properties of the viscous fluid, friction, and creep dissipator. In addition, calculations are made for the design parameters of each dissipator, and it is modeled as required for the case study. (iii) the new drifts and the damping values that the building presents for each dissipator are analyzed. According to the results obtained, the dissipator with the best results is of the flow type, since it has better performance in drifts and manages to produce an average damping of 96.87% for tall buildings. While the viscous dissipators obtain a 57.85% damping and the friction ones are estimated at 81.57%.